Green cash flow: how ESG performance shapes corporate cash holding strategies - Yuan, Leihong; Nor, Mohamad Naimi Mohamad; Kadir, Dzarfan Abdul (Frontiers in Sustainability, 2025)
This research explores the effect of environmental, social, and corporate governance (ESG) performance on cash holdings using panel data from A-share listed firms in China between 2018 and 2023. The results show that firms with good ESG performance are positively associated with corporate cash holdings; however, the relationship is of relatively low magnitude. Moreover, this study finds that internal control can mediate the relationship between ESG performance and cash holdings. It provides empirical insights to help firms optimize ESG strategies, enhance financial stability, and improve cash management through effective internal controls and managerial mechanisms, supporting policymakers, investors, and businesses in adapting to China’s evolving ESG regulations and sustainability goals. Furthermore, this study is among the first to incorporate internal control mechanisms to effectively influence the effect of ESG performance on corporate cash holdings efficiently in emerging economies, including China.